2AB protein of Senecavirus A antagonizes selective autophagy and type I interferon production by degrading LC3 and MARCHF8. Issue 8 (3rd August 2022) - Sun, Dage; Kong, Ning; Dong, Sujie; Chen, Xiaoyong; Qin, Wenzhen; Wang, Hua; Jiao, Yajuan; Zhai, Huanjie; Li, Liwei; Gao, Fei; Yu, Lingxue; Zheng, Hao; et al.
ABSTRACT: Senecavirus A (SVA), an important emerging porcine virus, has outbreaks in different regions and countries each year, becoming a virus with global prevalence. SVA infection has been reported to induce macroautophagy/autophagy; however, the molecular mechanisms of autophagy induction and the effect of SVA on autophagy remain unknown. This study showed that SVA infection induced the autophagy process in the early stage of SVA infection, and the rapamycin-induced autophagy inhibited SVA replication by degrading virus 3 C protein. To counteract this, SVA utilized 2AB protein inhibiting the autophagy process from promoting viral replication in the late stage of SVA infection. Further study showed that SVA 2AB protein interacted with MARCHF8/MARCH8 and LC3 to degrade the latter and inhibit the autophagy process. In addition, we found that MARCHF8 was a positive regulator of type I IFN (IFN-I) signaling. During the autophagy process, the SVA 2AB protein targeted MARCHF8 and MAVS forming a large complex for degradation to deactivate IFN-I signaling. Together, our study reveals the molecular mechanisms of selective autophagy in the host against viruses and reveals potential viral strategies to evade the autophagic process and IFN-I signaling for successful pathogenesis. Abbreviations: Baf A1 : bafilomycin A1 ; Co-IP: co-immunoprecipitation; CQ: chloroquine; DAPI: 4′, 6-diamidino-2-phenylindole; hpi: hours post-infection; IFN: interferon; ISG: IFN-stimulated gene; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MARCHF8/MARCH8: membrane associated ring-CH-type finger 8; MAVS: mitochondrial antiviral signaling protein; MOI: multiplicity of infection; Rapa: rapamycin; RT: room temperature; siRNA: small interfering RNA; SVA: Senecavirus A; TCID50 : 50% tissue culture infectious doses.